A new species of Vespula, and first record of Vespa crabro L. (Hymenoptera: Vespidae) from Guatemala, Central America - Landolt, Peter J.; Sierra, José Monzón; Unruh, Thomas R.; Zack, Richard S. (Zootaxa, 2010)
Vespula akrei Landolt sp. nov. is described from Guatemala. The first record of Vespa crabro L. in Guatemala is given, and Vespula inexspectata Eck from Mexico is re-described. We place Vespula akrei sp. nov. in the Vespula vulgaris (L.) species group (= Paravespula Bluthgen) based on morphology, color pattern, and DNA sequences from two mitochrondrial genes. It is presently known only from the Sierra de las Minas mountain range in southeastern Guatemala.